Fall 1989. - Kunsthandel Wolfgang Werner KG, Bremen (New York : Helen Serger, la boetie, inc., 1989)
Modersohn-Becker, Paula ; Schiele, Egon ; Nolde, Emil ; Grosz, Georg ; Rozanova, Olag ; Schwitters, Kurt ; Péri, Lasló ; Freundlich, Otto ; etc.
Fall 1989: the works of art illustrated in this catalogue are available for viewing partly in New York and partly in Bremen, 1989
boek